A comparison of the efficacy of multiple ultraviolet light room decontamination devices in a radiology procedure room. (30th January 2019) - Cadnum, Jennifer L.; Jencson, Annette L.; Gestrich, Scott A.; Livingston, Scott H.; Karaman, Boris A.; Benner, Kevin J.; Wilson, Brigid M.; Donskey, Curtis J.
Abstract: Objective: To evaluate the efficacy of multiple ultraviolet (UV) light decontamination devices in a radiology procedure room. Design: Laboratory evaluation. Methods: We compared the efficacy of 8 UV decontamination devices with a 4-minute UV exposure time in reducing recovery of methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), and Clostridium difficile spores on steel disk carriers placed at 5 sites on a computed tomography patient table. Analysis of variance was used to compare reductions for the different devices. A spectrometer was used to obtain irradiance measurements for the devices. Results: Four standard vertical tower low-pressure mercury devices achieved 2 log10 CFU or greater reductions in VRE and MRSA and ~1 log10 CFU reductions in C. difficile spores, whereas a pulsed-xenon device resulted in less reduction in the pathogens ( P <.001). In comparison to the vertical tower low-pressure mercury devices, equal or greater reductions in the pathogens were achieved by 3 nonstandard low-pressure mercury devices that included either adjustable bulbs that could be oriented directly over the exam table, a robotic base allowing movement along the side of the table during operation, or 3 vertical towers operated simultaneously. The low-pressure mercury devices produced primarily UV-C light, whereas the pulsed-xenon device produced primarily UV-A and UV-B light. The time required to move the devices from the corner of the room and set up for operation varied from 18 to 59 seconds. Conclusions: Many currently available UV devices could provide an effective and efficient adjunct to manual cleaning and disinfection in radiology procedure rooms.